2001
DOI: 10.1002/1097-0096(200102)29:2<92::aid-jcu1004>3.0.co;2-0
|View full text |Cite
|
Sign up to set email alerts
|

Utility of lower-extremity duplex sonography in patients with venous thromboembolism

Abstract: Purpose We evaluated the utility of venous duplex ultrasonography (VDUS) of the lower extremities in patients with pulmonary embolism (PE) and studied the distribution of venous thrombi in deep vein thrombosis (DVT) patients with and without PE. Methods We retrospectively reviewed medical records of all inpatients with a final diagnosis of PE or DVT between 1989 and 2000. Results Venous thrombosis was detected by VDUS in 229 patients (191 without PE and 38 with PE). The left leg only was involved in 50% of pat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
13
0
1

Year Published

2004
2004
2019
2019

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 40 publications
2
13
0
1
Order By: Relevance
“…Our study confirms the findings of a few cohort studies that have reported on the left-to-right ratio of DVT [9,10]. To our knowledge there are no studies that investigated whether BMI further increases this imbalanced distribution.…”
supporting
confidence: 91%
See 1 more Smart Citation
“…Our study confirms the findings of a few cohort studies that have reported on the left-to-right ratio of DVT [9,10]. To our knowledge there are no studies that investigated whether BMI further increases this imbalanced distribution.…”
supporting
confidence: 91%
“…This finding may explain the strong tendency of left‐ over right‐sided thrombosis observed in pregnant women, in whom 80–90% of deep venous thromboses occur in the left leg [7,8]. Some cohort studies among DVT patients also reported a higher incidence of thrombosis in the left than in the right leg, of approximately 60 vs. 40% [9,10].…”
Section: Distribution Of Risk Factors For Dvt In Patients With Left‐mentioning
confidence: 99%
“…Likewise, although contrast venography is considered the criterion standard for DVT, VDUS has become the ''standard of care.'' [4][5][6]13,14 Second, a study of consecutive patients would have eliminated possible selection bias, although the two previous prospective studies were also limited by convenience samples. It may be that those patients whom an EP-sonographer feels comfortable examining with US can be adequately assessed.…”
Section: Limitationsmentioning
confidence: 99%
“…Contrast venography is the criterion standard for diagnosing DVT, but it is invasive and has been replaced by venous duplex ultrasonography (VDUS) as the initial diagnostic test. [4][5][6] Recently, some centers have begun using computed tomography (CT) venography, with comparable results. [7][8][9] Although most emergency departments (EDs) are able to obtain VDUS during business hours, this often requires patients' being gone from the ED for several hours.…”
mentioning
confidence: 99%
“…Blebea found that 75% of laboratories routinely perform unilateral scans for DVT 10 . The policy of only scanning the symptomatic limb in patients who present with unilateral symptoms is supported by many published studies 11−18 . Other investigators disagree with this policy, finding that a significant number of patients had DVT located in the asymptomatic contralateral limb 19−21 .…”
Section: Introductionmentioning
confidence: 99%